Posttraumatic Growth in Breast Cancer Survivors: Constructive and Illusory Aspects. Issue 3 (26th May 2015) - Pat‐Horenczyk, Ruth; Perry, Shlomit; Hamama‐Raz, Yaira; Ziv, Yuval; Schramm‐Yavin, Sarit; Stemmer, Salomon M.
Abstract: This study investigated the impact of a building‐resilience intervention on coping and posttraumatic growth (PTG) in a convenience sample of 94 breast cancer survivors. PTG was divided into constructive and illusory components, based on the two‐sided Janus face model (Maercker & Zoellner, 2004). We operationalized constructive PTG as an improvement in both PTG and coping, and illusory PTG as an improvement in PTG only. An 8‐session group intervention was delivered to 49 women (mean age = 51.5 years, SD = 10.7) who completed self‐report questionnaires at baseline and at 6 months follow‐up; a control group of 45 women only completed questionnaires. More than half the participants ( n = 53; 56.38%) reported increased PTG at 6 months (mean change = 0.56, SD = 0.48, η 2 = .58). The increase in both PTG and positive coping was significantly greater in the intervention group than the control group ( B = 0.23 for PTG, and B = 0.35 for positive coping). Further, a higher proportion of constructive PTG (vs. illusory PTG) was reported by the participants in the intervention group (89.3%), as compared to the control group (56.3%; z = 2.57). The distinction between constructive and illusory PTG has clinical implications for interventions promoting coping and growth among cancer survivors.